The History and Function of Sisterhood in Turkey: Bacıyan-ı Rum Organization in Medieval Era - Bulut, Sefa (Sawwa: Jurnal Studi Gender, 2021)
Bacıyan-ı Rum (Anatolian Sisters Organization) is known as the world’s first women’s organization in history, but very few pieces of literature exist about this medieval organization. Thus, the aim was to reach up to all available historical documents about the topic and systematically analyze the nature and function of such an organization in the medieval era. Preliminary findings show that no written documents existed in English nor other languages except the Turkish language. It was also observed that this topic has emerged as an exciting area for many disciplines recently, leading to a sudden development of recent write-ups on such a topic. Therefore, awareness of gender roles in Turkish society, especially in the historical context of the Bacıyan-ı Rum Organization, is very important to be elaborated to form complete awareness of gender roles in society. In addition, awareness of the role of gender is excavated from various literature, both histories, economics, politics, travelogues, art, sociology, and anthropology to provide an extensive and detailed understanding of such remarkable phenomenal women organizations that existed in the Islamic world of the Medieval Era in Anatolia, Turkey.